The role of glutathione in the toxicity of styrene. - Parkki, Max G. (Scandinavian Journal of Work, Environment & Health, 1978)
The role of glutathione in the toxicity of styrene has been proposed based on the observations that glutathione inhibits the covalent binding of styrene and styrene oxide in vitro and that the administration of these compounds to animals decreases the glutathione content in the liver in vivo. In this study methionine (a precursor of reduced glutathione) or diethylmaleate (a depletor or reduced glutathione) was administered to hamsters concomitantly with styrene. Methionine protected the liver against the hepatotoxicity of styrene as indicated by the serum alanine aminotransferase activity. Diethylmaleate potentiated the hepatotoxic effect of styrene. A threshold value for hepatic glutathione of about 1 mmol/l was found for styrene toxicity. Cell damage occurred when the concentration of reduced glutathione in the liver has a central role in the development of cell damage caused by styrene.
Keywords: diethylmaleate; glutathione; hepatotoxicity; methionine; styrene; toxicity